Rooting characteristics and responses of photosynthesis to irrigation deficit of two hybrid bluegrasses, Kentucky bluegrass, and tall fescue - Su, Kemin; Bremer, Dale J.; Keeley, Steven J.; Fry, Jack D. (My University, 2009)
Drought stress is common among cool-season turfgrasses during summer in the U.S. transition zone. A two-year field study was conducted near Manhattan, Kansas, USA, to evaluate rooting characteristics and effects of drought on canopy physiology and appearance of ‘Apollo’ Kentucky bluegrass (Poa pratensis L.) (KBG), ‘Dynasty’ tall fescue (Festuca arundincea Schreb.) (TF), and two hybrid bluegrasses (HBG) ‘Reveille’ and ‘Thermal Blue’; HBG are genetic crosses between native Texas bluegrass (Poa arachnifera Torr.) and KBG. Rooting characteristics were measured in the field and greenhouse under well-watered conditions to evaluate root contributions to drought avoidance. Two irrigation treatments in the field included: 1) 60% (water-deficit); and 2) 100% (well-watered) evapotranspiration (ET) replacement. Ninety to 96% of all root length (0-80 cm) in the field and 74 to 80% of all root length (0-120 cm) in the greenhouse were in the upper 30 cm among Thermal Blue, Reveille, and KBG while in TF, only 86% and 70% of all root length in the field and greenhouse, respectively, were in the top 30 cm. In the field, tall fescue had 3 to 12 times greater root length in the lower profile (60-80 cm) among turfgrasses. Visual quality and gross photosynthesis (P[subscript]g) were greatest in TF among turfgrasses in both irrigation treatments. Reveille used more water from the 0-50 cm profile and performed better than Thermal Blue during water-deficit, but both HBG recovered from water-deficit slightly faster than KBG. Performances in visual quality and Pg generally ranked: TF > Reveille ≥ Thermal Blue = KBG.
Keywords: Heat-pulse technique; Soil-water content; Tall fescue; Kentucky bluegrass; Probe; Evapotranspiration; Avoidance; Prairie